Проблеми слов’янської фонотактики - Хоменко, Л.; Іщенко, О. (Iнститут української мови НАН України, 2009)
The article contains some information about the conference «Zagadnienia słowiańskiej fonotaktyki», which took place on 17 — 18 February 2009 at the M. Kopernik University’s Institute of Slavonic Philology (Тоrun, Poland).